Simulated Warming Differentially Affects the Growth and Competitive Ability of Centaurea maculosa Populations from Home and Introduced Ranges - He, Wei-Ming; Li, Jing-Ji; Peng, Pei-Hao (PLOS ONE, 2012)
Climate warming may drive invasions by exotic plants, thereby raising concerns over the risks of invasive plants. However, little is known about how climate warming influences the growth and competitive ability of exotic plants from their home and introduced ranges. We conducted a common garden experiment with an invasive plant Centaurea maculosa and a native plant Poa pratensis, in which a mixture of sand and vermiculite was used as a neutral medium, and contrasted the total biomass, competitive effects, and competitive responses of C. maculosa populations from Europe (home range) and North America (introduced range) under two different temperatures. The warming-induced inhibitory effects on the growth of C. maculosa alone were stronger in Europe than in North America. The competitive ability of C. maculosa plants from North America was greater than that of plants from Europe under the ambient condition whereas this competitive ability followed the opposite direction under the warming condition, suggesting that warming may enable European C. maculosa to be more invasive. Across two continents, warming treatment increased the competitive advantage instead of the growth advantage of C. maculosa, suggesting that climate warming may facilitate C. maculosa invasions through altering competitive outcomes between C. maculosa and its neighbors. Additionally, the growth response of C. maculosa to warming could predict its ability to avoid being suppressed by its neighbors.